Determination of toxic metals in water of lahor canal by atomic absorption spectroscopy - Mumtaz, M.W.; Adnan, A.; Mukhtar, H.; Danish, M.; Raza, M.A. (Химия и технология воды, 2015)
Present study describes the atomic absorption spectro-photometric determination of metals (Ni, Cr, Zn, Fe, As and Cu) in the surface water of Lahore canal passing through the center of Lahore (city) Pakistan. Analysis showed that month wise average Ni, Zn and As concentrations lies within the National Environmental Quality Standards limits for these metals as designed by Environmental Protection Agency Pakistan, while Cr, Fe and Cu showed marked rise in their month wise average concentrations from their limiting values.